Identification and functional characterization of Penicillium marneffei pleiotropic drug resistance transporters ABC1 and ABC2 - Panapruksachat S. (2017)
© 2016, Â© The Author 2016. Published by Oxford University Press on behalf of The International Society for Human and Animal Mycology. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com. Penicilliosis caused by the dimorphic fungus Penicillium marneffei is an endemic, AIDS-defining illness and, after tuberculosis and cryptococcosis, the third most common opportunistic infection of AIDS patients in tropical Southeast Asia. Untreated, patients have poor prognosis; however, primary amphotericin B treatment followed by prolonged itraconazole prophylaxis is effective. To identify ATP-binding cassette (ABC) transporters that may play a role in potential multidrug resistance of P. marneffei, we identified and classified all 46 P. marneffei ABC transporters from the genome sequence. PmABC1 and PmABC2 were most similar to the archetype Candida albicans multidrug efflux pump gene CDR1. P. marneffei Abc1p (PmAbc1p) was functionally expressed in Saccharomyces cerevisiae, although at rather low levels, and correctly localized to the plasma membrane, causing cells to be fourfold to eightfold more resistant to azoles and many other xenobiotics than untransformed cells. P. marneffei Abc2p (PmAbc2p) was expressed at similarly low levels, but it had no efflux activity and did not properly localize to the plasma membrane. Interestingly, PmAbc1p mislocalized and lost its transport activity when cells were shifted to 37Â Â°C. We conclude that expression of PmAbc1p in S. cerevisiae confers resistance to several xenobiotics indicating that PmAbc1p may be a multidrug efflux pump.